Rubber composition for fender and fender using same
The rubber composition for fenders, featuring a high carbon black content and specific ratios of butadiene rubber, addresses the challenge of reducing manufacturing costs while ensuring easy buckling and deformation of support legs, resulting in cost-effective and energy-absorbing fenders.
Patent Information
- Application Number
- JP2021099535
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-15
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2041-06-15
AI Technical Summary
Solid-type fenders face challenges in maintaining a simple three-dimensional shape while increasing the proportion of carbon black to reduce manufacturing costs, while also ensuring that the support legs are easily buckled and deformed to absorb energy effectively.
A rubber composition for fenders is developed, comprising crosslinkable rubber, a high proportion of carbon black (65-90 parts by mass per 100 parts by mass of rubber), and butadiene rubber (BR) in a ratio of 10-40 parts by mass, which facilitates easy buckling and deformation of the support legs while maintaining good rubber properties and reducing manufacturing costs.
The rubber composition enables the production of fenders that are prone to buckling and deformation at a lower cost, while maintaining excellent rubber properties and suppressing excessive reaction force, thus effectively absorbing energy and reducing damage to vessels or quays.
Smart Images

Figure 0007649454000011 
Figure 0007649454000012 
Figure 0007649454000013
Abstract
Description
[Technical field]
[0001] The present invention relates to a rubber composition for a fender to form a fender that is installed, for example, on a quay or the like and absorbs the energy of a ship or the like coming alongside, and to a solid-type fender comprising a cross-linked product of the rubber composition for a fender. [Background technology]
[0002] In solid-type fenders, the support legs, which elastically deform to absorb energy when a ship comes alongside, undergo buckling deformation during the elastic deformation, thereby suppressing excessive increases in reaction force while maintaining the amount of energy absorbed when the ship comes alongside (see Patent Document 1, etc.). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2002-013120 A [Patent Document 2] JP 2016-151095 A Summary of the Invention [Problem to be solved by the invention]
[0004] In the case of solid-type fenders, as described above, the support legs exhibit their rubber properties when a ship or other vessel comes alongside and undergo elastic deformation, resulting in buckling deformation. This prevents excessive increases in the reaction force generated in the fender, thereby preventing damage to the ship or vessel, the quay, or the fender itself. In order to make the support leg more susceptible to buckling deformation when coming alongside a ship or the like, the ratio of carbon black used as a reinforcing material to the rubber can be reduced, as can be inferred from the figures showing the compression rate-reaction force characteristics in the examples and comparative examples of Patent Document 1.
[0005] However, since solid-type fenders are huge lumps of rubber and require a large total amount of rubber, the compounded rubber needs to have a low unit price. In terms of manufacturing costs for the fenders, it is generally desirable to increase the proportion of carbon black, which is an inexpensive reinforcing material. However, as is clear from the results of the above figures, if the proportion of carbon black is increased, the support legs become less susceptible to buckling deformation, and the reaction force tends to increase.
[0006] Therefore, in order to make the support legs susceptible to buckling deformation even when the proportion of carbon black is increased, the support legs may be provided with a structure that makes them susceptible to buckling deformation, as described in Patent Document 2, for example. However, the above-mentioned structures often have complex three-dimensional shapes, as shown in, for example, FIG. 1 of Patent Document 2, and thus, in order to put a fender incorporating such a structure into practical use, it is difficult to design it and it is not easy to manufacture, which leads to an increase in the manufacturing costs of the fender.
[0007] It is essential that the support legs maintain a simple three-dimensional shape and contain a large proportion of carbon black to reduce the manufacturing costs of the fender, while still allowing the support legs to easily buckle and deform. The object of the present invention is to provide a rubber composition for a fender which has good rubber properties and can be used to produce a fender, the support legs of which are prone to buckling deformation when a ship or the like comes alongside, more cost-effectively, and a fender using the rubber composition. [Means for solving the problem]
[0008] The present invention relates to a rubber composition for a fender, which comprises a cross-linkable rubber, 65 parts by mass or more and 90 parts by mass or less of carbon black per 100 parts by mass of the total amount of the rubber, and a cross-linking component for cross-linking the rubber, wherein the rubber contains butadiene rubber in an amount of 10 parts by mass or more and 40 parts by mass or less per 100 parts by mass of the total amount of the rubber. The present invention also relates to a fender including a support leg that is elastically deformed when a ship or the like comes alongside, and at least the support leg is made of a crosslinked product of the rubber composition for fenders of the present invention. Effect of the Invention
[0009] According to the present invention, it is possible to provide a rubber composition for fenders which has good rubber properties and enables fenders, the support legs of which are prone to buckling deformation when a ship or the like comes alongside, to be produced more cost-effectively, and a fender using the same. [Brief description of the drawings]
[0010] [Figure 1] FIG. 2 is an end view showing the appearance of a model of a lambda-type fender produced for measuring the compression ratio-reaction force characteristics in the examples and comparative examples of the present invention. [Diagram 2] 2 is a graph showing the compressibility-reaction force characteristics obtained by forming the model of FIG. 1 using the rubber composition for a fender of Example 1. [Diagram 3] 2 is a graph showing the compressibility-reaction force characteristics obtained by forming the model of FIG. 1 using the rubber composition for a fender of Example 2. [Figure 4] 2 is a graph showing the compressibility-reaction force characteristics obtained by forming the model of FIG. 1 using the rubber composition for a fender of Example 3. [Diagram 5] 2 is a graph showing the compressibility-reaction force characteristics obtained by forming the model of FIG. 1 using the rubber composition for a fender of Example 4. [Figure 6] 2 is a graph showing the compressibility-reaction force characteristics obtained by forming the model of FIG. 1 using the rubber composition for a fender of Comparative Example 1. [Figure 7] 2 is a graph showing the compressibility-reaction force characteristics obtained by forming the model of FIG. 1 using the rubber composition for a fender of Comparative Example 2. [Figure 8] 2 is a graph showing the compressibility-reaction force characteristics obtained by forming the model of FIG. 1 using the rubber composition for a fender of Comparative Example 3. [Figure 9] 2 is a graph showing the compressibility-reaction force characteristics obtained by forming the model of FIG. 1 using the rubber composition for a fender of Comparative Example 4. [Figure 10]2 is a graph showing the compressibility-reaction force characteristics obtained by forming the model of FIG. 1 using the rubber composition for a fender of Comparative Example 5. [Figure 11] 2 is a graph showing the compressibility-reaction force characteristics obtained by forming the model of FIG. 1 using the rubber composition for a fender of Comparative Example 6. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] <Rubber composition for fender> As described above, the rubber composition for fenders of the present invention contains a cross-linkable rubber, 65 parts by mass or more and 90 parts by mass or less of carbon black per 100 parts by mass of the total amount of the rubber, and a cross-linking component for cross-linking the rubber, and the rubber is characterized in that it contains butadiene rubber (BR) in an amount of 10 parts by mass or more and 40 parts by mass or less per 100 parts by mass of the total amount of the rubber.
[0012] As explained above, in order to make the support legs of the fender more susceptible to buckling deformation, the ratio of carbon black to rubber can be reduced. However, in that case, the amount of rubber becomes relatively large, which increases the manufacturing costs of the rubber composition for the fender and, ultimately, the fender itself. On the other hand, if the proportion of carbon black is increased in order to reduce manufacturing costs, the rubber properties of the fender deteriorate, making it impossible to obtain good compression rate-reaction force characteristics for the fender, and also making the support legs less susceptible to buckling deformation.
[0013] Thus, the ratio of carbon black to rubber is the main factor affecting whether or not the support leg is susceptible to buckling deformation. However, according to the inventors' research, it is not only the proportion of carbon black that affects the susceptibility or resistance of the support leg to buckling deformation, but also the type of rubber and, when two or more types of rubber are used, their mixing ratio.
[0014] Therefore, the inventors further studied the type of rubber and found that it is sufficient to use a rubber containing BR in the above-mentioned predetermined ratio as the rubber. In other words, the support leg maintains a simple three-dimensional shape, while the proportion of carbon black is set to 65 parts by mass or more per 100 parts by mass of total rubber to reduce the manufacturing costs of the fender, while the BR is contained in an amount of 10 parts by mass or more per 100 parts by mass of total rubber, making it easier for the support leg to buckle and deform.
[0015] Furthermore, it is possible to suppress an excessive increase in the reaction force generated in the fender when a ship or the like comes alongside, thereby preventing damage to the ship or the like, the quay, or the fender itself. However, if the proportion of BR exceeds the range of 40 parts by mass or less per 100 parts by mass of the total amount of rubber, the rubber physical properties of the fender may decrease, and the fender may not be able to obtain good compression rate-reaction force characteristics, although this depends on the type of other rubber used in combination.
[0016] In contrast, by setting the proportion of carbon black to 90 parts by mass or less per 100 parts by mass of the total amount of rubber and setting the proportion of BR to 40 parts by mass or less per 100 parts by mass of the total amount of rubber, the rubber physical properties of the fender can be improved. This makes it possible to impart good compression ratio-reaction force characteristics to the fender. These facts are also evident from the results of the examples and comparative examples described below.
[0017] <Rubber> As the rubber, BR is used in combination with another crosslinkable rubber capable of crosslinking together with the BR. (BR) As the BR, any of various BRs having a polybutadiene structure in the molecule and having crosslinking properties can be used.
[0018] In particular, high-cis BR having a cis-1,4 bond content of 95% or more is preferred, since it exhibits little change in physical properties due to temperature and has stable compression modulus-reaction force characteristics. In addition, there are two types of BR: oil-extended, in which flexibility is adjusted by adding an extender oil, and non-oil-extended, in which no extender oil is added. Either type of BR can be used in the present invention. As specific examples of the non-oil-extended high-cis BR, for example, one or more of the following various BRs can be used.
[0019] UBEPOL (registered trademark) BR150 (cis-1,4 bond content: 98% by mass), BR130B (cis-1,4 bond content: 96% by mass), BR150B (cis-1,4 bond content: 97% by mass), BR360B (cis-1,4 bond content: 98% by mass), BR150L (cis-1,4 bond content: 98% by mass), BR360L (cis-1,4 bond content: 98% by mass), BR230 (cis-1,4 bond content: 98% by mass), and BR710 (cis-1,4 bond content: 98% by mass), manufactured by Ube Industries, Ltd.
[0020] A specific example of the oil-extended high-cis BR is UBEPOL BR133P (cis-1,4 bond content: 98 mass %, oil amount: 37.5 phr) manufactured by Ube Industries, Ltd. One or more of these non-oil-extended and / or oil-extended BRs can be used.
[0021] (other rubber) Examples of other rubbers that can be used in combination with BR include natural rubber, styrene butadiene rubber (SBR), isoprene rubber (IR), butyl rubber (IIR), ethylene propylene diene rubber (EPDM), chloroprene rubber (CR), chlorosulfonated polyethylene (CSM), acrylonitrile butadiene rubber (NBR), hydrogenated acrylonitrile butadiene rubber (HNBR), acrylic rubber (ACM), fluororubber (FKM), epichlorohydrin rubber, and the like.
[0022] In particular, natural rubber is preferred in order to impart good compression rate-reaction force characteristics to the fender. Examples of natural rubber include various grades of natural rubber such as TSR-20 and RSS#3, and also deproteinized natural rubber can be used. One or more of these other rubbers can be used. In particular, considering the need to manufacture fenders at lower cost, which have good rubber physical properties and whose support legs are susceptible to buckling deformation when a ship or other vessel comes alongside, it is preferable to use only two types of rubber, BR and natural rubber (including the use of two or more types of BR and natural rubber in combination).
[0023] (Rubber ratio) As described above, the proportion of BR is limited to 10 parts by mass or more and 40 parts by mass or less in 100 parts by mass of the total amount of rubber. The reason for this is as explained above. In order to further improve the effects of the present invention described above, even within the above range, the proportion of BR is preferably 13 parts by mass or more, and particularly preferably 20 parts by mass or more, per 100 parts by mass of the total amount of rubber, and is preferably 37 parts by mass or less, and particularly preferably 35 parts by mass or less.
[0024] When only two types of rubber, BR and natural rubber, are used together, the proportion of natural rubber is the remaining amount of BR. 。
[0025] When two or more kinds of other rubbers are used in combination with BR, the ratios of the two or more kinds of other rubbers to be used in combination may be set so that the total ratio of the other rubbers is the remaining amount of BR. Carbon Black As the carbon black, various carbon blacks capable of functioning as a rubber filler (filling agent, reinforcing agent), such as furnace black, acetylene black, and ketjen black, can be used.
[0026] Specific examples of carbon black include, but are not limited to, the following carbon blacks: From the SEAT (registered trademark) series manufactured by Tokai Carbon Co., Ltd., SEAT 9H (SAF-HS, nitrogen adsorption specific surface area: 142 m 2 / g], SEAT 9 [SAF, nitrogen adsorption specific surface area: 142 m 2 / g], SEAT 7HM [N234, nitrogen adsorption specific surface area: 126 m 2 / g], Seast 6 [ISAF, nitrogen adsorption specific surface area: 119 m 2 / g], SEAT 600 [ISAF-LS, nitrogen adsorption specific surface area: 106 m 2 / g], SEAT 5H [IISAF, nitrogen adsorption specific surface area: 99 m 2 / g], Seest KH [N399, nitrogen adsorption specific surface area: 93 m 2 / g], SEAT 3H [HAF-HS, nitrogen adsorption specific surface area: 82 m 2 / g], SEAT NH [N351, nitrogen adsorption specific surface area: 74 m 2 / g], SEAT 3 [HAF, nitrogen adsorption specific surface area: 79 m 2 / g], SEAT N [LI-HAF, nitrogen adsorption specific surface area: 74 m 2 / g], SEAT 300 [HAF-LS, nitrogen adsorption specific surface area: 84 m 2 / g], SEAT 116HM [MAF-HS, nitrogen adsorption specific surface area: 56 m 2 / g], SEAT 116 [MAF, nitrogen adsorption specific surface area: 49 m 2 / g], seast SO〔FEF, nitrogen adsorption specific surface area: 42m 2 / g], Seast V [GPF, nitrogen adsorption specific surface area: 27m 2 / g], SEAT SVH [SRF-HS, nitrogen adsorption specific surface area: 32 m 2 / g], Seest FY [SRF-HS, nitrogen adsorption specific surface area: 29 m 2 / g], SEAT S [SRF, nitrogen adsorption specific surface area: 27 m 2 / g], SEAT SP [SRF-LS, nitrogen adsorption specific surface area: 23 m 2 / g], SEAT TA [FT class, nitrogen adsorption specific surface area: 19m 2 / g]
[0027] Asahi #95 (nitrogen adsorption specific surface area: 147 m) manufactured by Asahi Carbon Co., Ltd. 2 / g], Asahi #80 [ISAF, nitrogen adsorption specific surface area: 115 m 2 / g], Asahi #70 [HAF, nitrogen adsorption specific surface area: 77 m 2 / g], Asahi #70L [Nitrogen adsorption specific surface area: 84 m 2 / g], Asahi AX-015 [Nitrogen adsorption specific surface area: 145 m 2 / g], Asahi F-200GS [Nitrogen adsorption specific surface area: 51 m 2 / g], Asahi #65 [Nitrogen adsorption specific surface area: 42 m 2 / g], Asahi #60HN [Nitrogen adsorption specific surface area: 48 m 2 / g], Asahi #60U [Nitrogen adsorption specific surface area: 43 m 2 / g], Asahi #55 [Nitrogen adsorption specific surface area: 26 m 2 / g], Asahi #50HG [Nitrogen adsorption specific surface area: 20m 2 / g], Asahi #52 [Nitrogen adsorption specific surface area: 28 m 2 / g], Asahi #51 [Nitrogen adsorption specific surface area: 20 m 2 / g], Asahi #50U [Nitrogen adsorption specific surface area: 27 m 2 / g], Asahi #50 [Nitrogen adsorption specific surface area: 23 m 2 / g], Asahi #35 [Nitrogen adsorption specific surface area: 24 m 2 / g], Asahi #22K [Nitrogen adsorption specific surface area: 21 m 2 / g], Asahi #15HS [Nitrogen adsorption specific surface area: 14 m 2 / g], Asahi #15 [Nitrogen adsorption specific surface area: 12 m 2 / g], Asahi #8 [Nitrogen adsorption specific surface area: 12 m 2 / g], Asahi Thermal [Nitrogen adsorption specific surface area: 24 m 2 / g]
[0028] One or more of these carbon blacks can be used. In particular, as the carbon black, it is preferable to use furnace black such as SAF, ISAF, HAF, MAF, FEF, GPF, or SRF. <Carbon black ratio> As mentioned above, the proportion of carbon black is limited to 65 parts by mass or more and 95 parts by mass or less per 100 parts by mass of the total amount of rubber.
[0029] If the proportion of carbon black is less than this range, the proportion of rubber will be relatively high, resulting in increased production costs for the rubber composition for the fender and, ultimately, for the fender. In contrast, by setting the proportion of carbon black to the above range or more, the amount of rubber can be relatively reduced, thereby reducing the production costs of the rubber composition for a fender and, ultimately, the fender.
[0030] On the other hand, if the proportion of carbon black exceeds the above range, the reinforcing properties of the rubber due to the carbon black will be too strong and the cross-linked product itself will be too hard, which may make it difficult for the support legs to buckle. Furthermore, the viscosity of the rubber composition for a fender before crosslinking may increase, resulting in reduced processability.
[0031] Furthermore, it may become difficult to knead the various components to prepare the rubber composition for the fender, or to knead the rubber composition for the fender or mold it into any three-dimensional shape to produce the fender. In contrast, by setting the proportion of carbon black within the above range, the reinforcing properties of the rubber can be prevented from becoming too strong and the cross-linked product itself can be prevented from becoming too hard, making the support leg more susceptible to buckling deformation.
[0032] In addition, it is also possible to suppress a decrease in the processability of the rubber composition for a fender. In order to further improve these effects, the amount of carbon black is preferably not more than 90 parts by mass, particularly preferably not more than 85 parts by mass, per 100 parts by mass of the total amount of rubber, even within the above range. When two or more types of carbon black are used in combination, the total proportion thereof may be within the above range.
[0033] When two or more types of carbon black are used in combination, for example, a carbon black having a large nitrogen adsorption specific surface area and a strong reinforcing effect on rubber may be used in combination with a carbon black having a small nitrogen adsorption specific surface area and a weaker reinforcing effect. In this case, the overall proportion of carbon black can be maintained, and the reinforcing properties of the rubber can be weakened while suppressing an increase in the manufacturing cost of the fender.
[0034] In addition, the support leg can be made more susceptible to buckling deformation, and the deterioration of the processability of the rubber composition for a fender can be more effectively suppressed. <Crosslinking component> Examples of the crosslinking component for crosslinking the rubber include a crosslinking agent and a crosslinking accelerator. (Crosslinking agent) Examples of the crosslinking agent include sulfur-based crosslinking agents and peroxide-based crosslinking agents, with sulfur-based crosslinking agents being particularly preferred.
[0035] Examples of the sulfur-based crosslinking agent include powdered sulfur, powdered sulfur in oil, precipitated sulfur, colloidal sulfur, dispersible sulfur, and other sulfur-containing organic compounds such as tetramethylthiuram disulfide and N,N-dithiobismorpholine, with sulfur being particularly preferred. The amount of sulfur is preferably at least 0.5 parts by mass, particularly preferably at least 0.7 parts by mass, and is preferably at most 3 parts by mass, particularly preferably at most 2 parts by mass, per 100 parts by mass of the total amount of rubber.
[0036] If the proportion of sulfur is less than this range, the crosslinking rate of the rubber composition for a fender as a whole becomes slow, and the time required for crosslinking becomes long, which may result in a decrease in productivity of the fender. Furthermore, if the proportion of sulfur exceeds the above range, the compression set after crosslinking may become large, or the excess sulfur may bloom on the surface of the fender. When using, for example, oil-containing powdered sulfur, dispersible sulfur, or the like, the above ratio refers to the ratio of sulfur itself as an active ingredient contained therein.
[0037] When an organic sulfur-containing compound is used as a crosslinking agent, the proportion thereof is preferably adjusted so that the proportion of sulfur contained in the molecule per 100 parts by mass of the total amount of rubber falls within the above range. (Crosslinking accelerator) Examples of the crosslinking accelerator include inorganic accelerators such as slaked lime, magnesia (MgO), litharge (PbO), etc., and the following various organic accelerators, which may be used alone or in combination.
[0038] Guanidine accelerators such as 1,3-di-o-tolylguanidine, 1,3-diphenylguanidine, 1-o-tolylbiguanide, and di-o-tolylguanidine salts of dicatechol borate. Thiazole accelerators such as 2-mercaptobenzothiazole and di-2-benzothiazolyl disulfide.
[0039] Sulfenamide accelerators such as N-tert-butyl-2-benzothiazolylsulfenamide and N-cyclohexyl-2-benzothiazolylsulfenamide. Thiuram accelerators such as tetramethylthiuram monosulfide, tetramethylthiuram disulfide, tetraethylthiuram disulfide, and dipentamethylenethiuram tetrasulfide.
[0040] Dithiocarbamate accelerators such as zinc dimethyldithiocarbamate, zinc diethyldithiocarbamate, and zinc dibutyldithiocarbamate. Thiourea accelerators such as N,N'-diphenylthiourea, trimethylthiourea, and N,N'-diethylthiourea. The proportion of the crosslinking accelerator can be set arbitrarily depending on the type, but it is usually preferably at least 0.1 part by mass, particularly preferably at least 0.5 part by mass, and at most 5 parts by mass, particularly preferably at most 4 parts by mass, per 100 parts by mass of the total amount of rubber.
[0041] <others> The rubber composition for fenders may further contain fillers other than carbon black, antioxidants, crosslinking assistants, plasticizers, waxes, colorants, tackifiers, etc. in any proportion, as required. (Other fillers) Examples of fillers other than carbon black include silica.
[0042] (Anti-aging agent) The antioxidant may be one or more of various antioxidants classified according to their main functions, such as weather-resistant antioxidants and heat-resistant antioxidants. Examples of the antioxidant include N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine and 2,2,4-trimethyl-1,2-dihydroquinoline polymers.
[0043] In particular, N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine is preferred because of its excellent effect of preventing cracking due to sunlight, ozone, and bending cracking. The proportion of the antioxidant is preferably at least 0.1 part by mass, particularly preferably at least 0.5 part by mass, and is preferably at most 7 parts by mass, particularly preferably at most 5 parts by mass, per 100 parts by mass of the total amount of rubber.
[0044] (Crosslinking aid) Examples of the crosslinking aid include metal compounds such as zinc oxide; fatty acids such as stearic acid, oleic acid, cottonseed fatty acid, and other conventionally known crosslinking aids, and the like. The proportion of the crosslinking aid is preferably at least 0.1 part by mass, particularly preferably at least 0.5 part by mass, and is preferably at most 8 parts by mass, particularly preferably at most 6 parts by mass, per 100 parts by mass of the total amount of rubber.
[0045] (Plasticizer) The plasticizer may be, for example, oil or liquid rubber. Among these, the oil may be, but is not limited to, one or more of various grades of oil such as Diana (registered trademark) process oil PW, NH, NP, NS, NR, NM, AC, and AH manufactured by Idemitsu Kosan Co., Ltd.
[0046] Examples of the liquid rubber include one or more of liquid isoprene rubber, hydrogenated liquid isoprene rubber, liquid butadiene rubber, liquid styrene butadiene rubber, and end-modified products thereof. The proportion of the plasticizer is preferably at least 1 part by mass, particularly preferably at least 3 parts by mass, per 100 parts by mass of the total amount of rubber, and is preferably at most 30 parts by mass, particularly preferably at most 13 parts by mass.
[0047] (wax) Examples of waxes include, but are not limited to, OZOACE (registered trademark) 0355 manufactured by Nippon Seiro Co., Ltd., and SANNOC (registered trademark), SANNOC N, and SANNOC P manufactured by Ouchi Shinko Chemical Industry Co., Ltd. These waxes function in combination with antioxidants to prevent sun cracking and ozone cracking.
[0048] The proportion of the wax is preferably at least 0.1 part by mass, particularly preferably at least 0.5 part by mass, and is preferably at most 7 parts by mass, particularly preferably at most 5 parts by mass, per 100 parts by mass of the total amount of rubber. The rubber composition for fenders can be prepared, for example, by first kneading the above-mentioned components other than the crosslinking component using a kneader, Banbury mixer or the like, and then adding and kneading the crosslinking component.
[0049] The process for producing a fender using the prepared rubber composition for fenders may be the same as in the conventional process. That is, the fender can be produced by combining any steps such as molding, sheet molding, assembly, and crosslinking depending on the size and shape of the fender to be produced. 《Fender》 The fender of the present invention includes a support leg that is fixed to a quay or the like and elastically deforms when a ship or the like comes alongside, and is characterized in that at least the support leg is made of a cross-linked product of the rubber composition for fenders of the present invention.
[0050] Specific examples of the fender of the present invention include the following various fenders. An arch-shaped fender (including so-called inverted V-shaped, lambda (λ)-shaped and beta (β)-shaped) in which a head portion that constitutes the flat impact surface against which a ship or the like comes alongside, and a pair of support legs that hang down while spreading out in the fore-and-aft direction from the head portion are integrally formed from a cross-linked product of a rubber composition for fenders. A so-called kappa (κ) type fender in which a disk-shaped head and a truncated cone-shaped support leg that hangs down while expanding radially from the head are integrally formed by a cross-linked product of a rubber composition for fenders. A so-called π-type fender comprising a head portion made of steel or the like and a pair of support legs made of a cross-linked product of a rubber composition for fenders that hang down from the head portion while spreading out in the front-to-rear direction.
[0051] In any of these fenders, by forming at least the support legs from the crosslinked product of the rubber composition for fenders of the present invention described above, it is possible to make the fenders more susceptible to buckling deformation when coming alongside a ship or the like. Moreover, the proportion of rubber can be reduced, thereby reducing the manufacturing costs of the fender. In particular, the effect of reducing manufacturing costs is remarkable in arch-type or kappa-type fenders in which the entire fender, including not only the support legs but also the head portion, is integrally formed from the crosslinked product of the rubber composition for fenders of the present invention. EXAMPLES
[0052] The present invention will be further described below based on examples and comparative examples, but the configuration of the present invention is not necessarily limited to these examples. Example 1 The rubber used was a combination of 80 parts by mass of natural rubber (TSR20 product) and 20 parts by mass of non-oil-extended high-cis BR (UBEPOL BR150L manufactured by Ube Industries, Ltd., cis-1,4 bond content: 98% by mass).
[0053] A total of 100 parts by mass of both rubbers was kneaded together with the components shown in Table 1 below using a 3 L kneader.
[0054] [Table 1]
[0055] The components in Table 1 are as follows, and the parts by mass in the table are parts by mass per 100 parts by mass of the total amount of rubber. Carbon black (i): HAF, Seast 3 manufactured by Tokai Carbon Co., Ltd., nitrogen adsorption specific surface area: 79 m 2 / g Crosslinking aid I: Zinc oxide type 2, manufactured by Mitsui Mining & Smelting Co., Ltd. Crosslinking aid II: stearic acid, trade name Tsubaki manufactured by NOF Corporation Antioxidant: N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine, Nocrac (registered trademark) 6C manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Wax: Sannock manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Oil: Diana Process Oil NH-70S manufactured by Idemitsu Kosan Co., Ltd. Next, the crosslinking components shown in Table 2 below were added, and the mixture was further kneaded using an open roll to prepare a rubber composition for a fender.
[0056] [Table 2]
[0057] The components in Table 2 are as follows, and the parts by mass in the table are parts by mass per 100 parts by mass of the total amount of rubber. Crosslinking agent: Kinkajirushi 5% oil-filled fine sulfur manufactured by Tsurumi Chemical Industry Co., Ltd. Accelerator NS: N-tert-butyl-2-benzothiazolyl sulfenamide, a sulfenamide-based accelerator, Noccela (registered trademark) NS manufactured by Ouchi Shinko Chemical Industry Co., Ltd. The proportion of BR was 20 parts by mass per 100 parts by mass of the total amount of rubber, and the proportion of carbon black was 70 parts by mass per 100 parts by mass of the total amount of rubber.
[0058] Example 2 The rubber used was a combination of 65 parts by mass of natural rubber (TSR20 product) and 35 parts by mass of non-oil-extended high-cis BR (UBEPOL BR150B manufactured by Ube Industries, Ltd., cis-1,4 bond content: 97% by mass). A total of 100 parts by mass of both rubbers was kneaded together with the components shown in Table 3 below using a 3 L kneader.
[0059] [Table 3]
[0060] Carbon black (ii) in Table 3 is as follows. Carbon black (ii): ISAF, Seast 6 manufactured by Tokai Carbon Co., Ltd., nitrogen adsorption specific surface area: 119 m 2 / g The other components were the same as in Example 1, and the parts by mass in the table are parts by mass per 100 parts by mass of the total amount of rubber.
[0061] Next, the crosslinking components shown in Table 4 below were added, and further kneaded using an open roll to prepare a rubber composition for a fender.
[0062] [Table 4]
[0063] The components in Table 4 are the same as those in Example 1, and the parts by mass in the table are parts by mass per 100 parts by mass of the total amount of rubber. The proportion of BR was 35 parts by mass per 100 parts by mass of the total amount of rubber, and the proportion of carbon black was 65 parts by mass per 100 parts by mass of the total amount of rubber. Example 3 The rubber used was a combination of 70 parts by mass of natural rubber (TSR20 product) and 30 parts by mass of non-oil-extended high-cis BR (UBEPOL BR150 manufactured by Ube Industries, Ltd., cis-1,4 bond content: 98% by mass).
[0064] A total of 100 parts by mass of both rubbers was kneaded together with the components shown in Table 5 below using a 3 L kneader.
[0065] [Table 5]
[0066] Carbon black (iii) in Table 5 is as follows. Carbon black (iii): FEF, Seast SO manufactured by Tokai Carbon Co., Ltd., nitrogen adsorption specific surface area: 42 m 2 / g The other components were the same as in Example 1, and the parts by mass in the table are parts by mass per 100 parts by mass of the total amount of rubber.
[0067] Next, the crosslinking components shown in Table 6 below were added, and further kneaded using an open roll to prepare a rubber composition for a fender.
[0068] [Table 6]
[0069] The components in Table 6 are the same as those in Example 1, and the parts by mass in the table are parts by mass per 100 parts by mass of the total amount of rubber. The proportion of BR was 30 parts by mass per 100 parts by mass of the total amount of rubber, and the proportion of the two types of carbon black in total was 80 parts by mass per 100 parts by mass of the total amount of rubber. Example 4 The rubber used was a combination of 87 parts by mass of natural rubber (TSR20 product) and 13 parts by mass of non-oil-extended high-cis BR (UBEPOL BR150L manufactured by Ube Industries, Ltd., cis-1,4 bond content: 98% by mass).
[0070] A total of 100 parts by mass of both rubbers was kneaded together with the components shown in Table 7 below using a 3 L kneader.
[0071] [Table 7]
[0072] The components in Table 7 are the same as those in Example 3, and the parts by mass in the table are parts by mass per 100 parts by mass of the total amount of rubber. Next, the crosslinking components shown in Table 8 below were added, and the mixture was further kneaded using an open roll to prepare a rubber composition for a fender.
[0073] [Table 8]
[0074] The components in Table 8 are the same as those in Example 1, and the parts by mass in the table are parts by mass per 100 parts by mass of the total amount of rubber. The proportion of BR was 13 parts by mass per 100 parts by mass of the total amount of rubber, and the proportion of the two types of carbon black in total was 80 parts by mass per 100 parts by mass of the total amount of rubber. Comparative Example 1 A rubber composition for fenders was prepared in the same manner as in Example 1, except that 80 parts by mass of natural rubber (TSR20 product) and 20 parts by mass of non-oil-extended SBR (JSR1502 manufactured by JSR Corporation, bound styrene content: 23.5%) were used in combination as the rubber.
[0075] Comparative Example 2 A rubber composition for fenders was prepared in the same manner as in Example 2, except that 65 parts by mass of natural rubber (TSR20 product) and 35 parts by mass of non-oil-extended SBR (JSR1502 manufactured by JSR Corporation, bound styrene content: 23.5%) were used in combination as the rubber. Comparative Example 3 A rubber composition for fenders was prepared in the same manner as in Example 3, except that 70 parts by mass of natural rubber (TSR20 product) and 30 parts by mass of non-oil-extended SBR (JSR1502 manufactured by JSR Corporation, bound styrene content: 23.5%) were used in combination as the rubber.
[0076] Comparative Example 4 A rubber composition for fenders was prepared in the same manner as in Example 4, except that 87 parts by mass of natural rubber (TSR20 product) and 13 parts by mass of non-oil-extended SBR (JSR1502 manufactured by JSR Corporation, bound styrene content: 23.5%) were used in combination as the rubber. Comparative Example 5 A rubber composition for a fender was prepared in the same manner as in Example 1, except that 50 parts by mass of natural rubber (TSR20 product), 30 parts by mass of a non-oil-extended high-cis BR (UBEPOL BR150L manufactured by Ube Industries, Ltd., cis-1,4 bond content: 98% by mass), and 20 parts by mass of a non-oil-extended low-cis BR (Diene (registered trademark) NF35R manufactured by Asahi Kasei Corporation, cis-1,4 bond content: 35% by mass) were used in combination as the rubber.
[0077] The total ratio of the two types of BR was 50 parts by mass per 100 parts by mass of the total amount of rubber, and the ratio of carbon black was 70 parts by mass per 100 parts by mass of the total amount of rubber. Comparative Example 6 A rubber composition for a fender was prepared in the same manner as in Example 1, except that 50 parts by mass of natural rubber (TSR20 product) and 50 parts by mass of non-oil-extended high-cis BR (UBEPOL BR150L manufactured by Ube Industries, Ltd., cis-1,4 bond content: 98% by mass) were used in combination as the rubber.
[0078] The proportion of BR was 50 parts by mass per 100 parts by mass of the total amount of rubber, and the proportion of carbon black was 70 parts by mass per 100 parts by mass of the total amount of rubber. <Type A durometer hardness measurement> The rubber compositions for fenders prepared in each of the Examples and Comparative Examples were press-crosslinked at 140° C. for 60 minutes to prepare crosslinked sheets having a thickness of 2 mm.
[0079] Next, three of the crosslinked sheets were stacked together to form a test piece for hardness measurement, and the test piece was subjected to the hardness test according to the Japanese Industrial Standard JIS K6253-3. :2012 Type A durometer hardness was measured according to the measurement method specified in "Vulcanized rubber and thermoplastic rubber - Determination of hardness - Part 3: Durometer hardness." The measurement temperature was the standard test temperature (23°C). Tensile Test The rubber compositions for fenders prepared in each of the Examples and Comparative Examples were press-crosslinked at 140° C. for 60 minutes to prepare crosslinked sheets having a thickness of 3 mm.
[0080] The crosslinked sheet was then punched out to conform to Japanese Industrial Standard JIS K6251. :2017 Dumbbell-shaped No. 3 test pieces were prepared as specified in "Vulcanized and thermoplastic rubber - Determination of tensile properties." The test pieces were then subjected to tensile tests as specified in the standard to measure the tensile strength T (MPa) and elongation at break E b (%) was calculated.
[0081] The measurement temperature was the standard test temperature (23°C). The tensile strength T was evaluated as follows: less than 16 MPa was evaluated as "x", 16 MPa or more but less than 20 MPa was evaluated as "○", and 20 MPa or more was evaluated as "◎". The elongation at break E b The evaluation criteria were as follows: less than 350% was rated as "X", 350% or more but less than 400% was rated as "○", and 400% or more was rated as "◎".
[0082] <Making a model of a fender> Using the rubber compositions for fenders prepared in each of the Examples and Comparative Examples, a miniature-sized model 1 of a lambda-type fender having an end face shape shown in FIG. 1 was produced. That is, a head 3 constituting a planar impact surface 2, a pair of support legs 4 hanging down from the head 3 while spreading out in the fore-and-aft direction, and a mounting flange 5 connected to the lower ends of the support legs 4 and protruding outward were integrally formed from a rubber composition for fenders and cross-linked to produce model 1.
[0083] The crosslinking conditions were 140°C x 120 minutes. The dimensions of each part were as follows: width W1 of head 3 was 65 mm, height H was 100 mm, width W2 between the tips of flange parts 5 was 180 mm, and total length was 200 mm. <Compression rate-reaction force characteristic test> The fender model 1 created above was compressed three times in the height direction at a speed of 15 mm / min at the standard test temperature (23°C) with a maximum compression of 52.5% of the height H, with a 3-minute interval between each compression.
[0084] The average value of the reaction force according to the compression ratio during the second and third compressions was then calculated, and the compression ratio-reaction force characteristics were calculated by plotting the compression ratio (%) on the horizontal axis and the reaction force (kN) on the vertical axis. The results of Example 1 are shown in Figure 2, the results of Example 2 in Figure 3, the results of Example 3 in Figure 4, the results of Example 4 in Figure 5, the results of Comparative Example 1 in Figure 6, the results of Comparative Example 2 in Figure 7, the results of Comparative Example 3 in Figure 8, the results of Comparative Example 4 in Figure 9, the results of Comparative Example 5 in Figure 10, and the results of Comparative Example 6 in Figure 11.
[0085] As seen in Figs. 5 to 11, it was found that the fenders made of the rubber compositions for fenders of Comparative Examples 1 to 4 did not buckle or deform when compressed, and the reaction force increased unilaterally depending on the compression rate. Therefore, Comparative Examples 1 to 4 were evaluated as "x" because there was no buckling deformation. On the other hand, although the fenders made of the rubber compositions for fenders in Examples 1 to 4 and Comparative Examples 5 and 6 all had the same shape as Comparative Examples 1 to 4, as can be seen in Figures 2 to 5, 10 and 11, the reaction force value decreased midway through the compression, indicating that buckling deformation occurred due to compression.
[0086] Therefore, Examples 1 to 4 and Comparative Examples 5 and 6 were rated as "good" because buckling deformation occurred. The above results are shown in Tables 9 and 10.
[0087] [Table 9]
[0088] [Table 10]
[0089] From the results of Examples 1 to 4 and Comparative Examples 1 to 4 in Tables 9 and 10, it was found that by forming at least the support leg of the fender from a rubber composition for fenders containing rubber containing BR and 65 to 90 parts by mass of carbon black per 100 parts by mass of the total amount of the rubber, it is possible to produce a fender that has good rubber properties as a rubber and whose support leg is prone to buckling deformation when a ship or the like comes alongside, at a lower cost.
[0090] However, from the results of Examples 1 to 4 and Comparative Examples 5 and 6, it was found that in order to obtain the above-mentioned effects, the proportion of BR needs to be 10 to 40 parts by mass per 100 parts by mass of the total amount of rubber, the BR is preferably high-cis BR having a cis-1,4 bond content of 95% or more, and the rubber is preferably a combination of two types, BR and natural rubber. [Explanation of symbols]
[0091] 1 Fender model 2 Impact surface 3 head 4 Support legs 5 Flange
Claims
1. The composition comprises a crosslinkable rubber, carbon black, a crosslinking component for crosslinking the rubber, and an antioxidant, Only two types of rubber, namely butadiene rubber and natural rubber, are used, and the compounding ratio of the butadiene rubber is 10 to 40 parts by mass per 100 parts by mass of the total amount of the rubber, and the natural rubber is 60 to 90 parts by mass per 100 parts by mass of the total amount of the rubber, with the balance of the butadiene rubber being the remainder; The carbon black is contained in an amount of 65 to 90 parts by mass per 100 parts by mass of the total amount of the rubber, The rubber composition for a fender contains the antioxidant in an amount of 0.1 to 7 parts by mass per 100 parts by mass of the total amount of the rubber.
2. 2. The rubber composition for a fender according to claim 1, wherein the butadiene rubber is a high-cis butadiene rubber having a cis-1,4 bond content of 95% or more.
3. A rubber composition for fenders as described in claim 1 or 2, wherein the carbon black contains two or more types of carbon black having different nitrogen adsorption specific surface areas.
4. A fender comprising a support leg that is elastically deformed when a ship or the like comes alongside, at least the support leg being made of a crosslinked product of the rubber composition for fenders according to any one of claims 1 to 3.
5. The fender according to claim 4, wherein the entire fender including the support leg is formed into an arch shape from the rubber composition for fenders.
Citation Information
Patent Citations
Support member for marine fender
EP0400237A1
Fender
JP2002013120A
Rubber composition for fender, and fender using the same
JP2010189495A
Manufacturing method for rubber composition
JP2010285470A
Fender
JP2016151095A